Evaluation of the Cell Viability Effects of Orthodontic Mini-Implants Coated with Zinc Oxide Nanoparticles: An In Vitro Study - Abdelmawla.A; M.S. Abd El-Sadek; Hashem A.Sh. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Success and long-term stability of orthodontic mini-implants rely on limiting the inflammation amount and inhibiting the microbes adhesion on the surface of the implanted devices. Zinc Oxide nanoparticles were known to be used as a coating on orthodontic mini-implants to decrease colonization and plaque formation. The mini-implants should be biocompatible because they are in contact with the mucosa and fluid of the oral cavity for a long time. This study aimed to assess the cell viability around orthodontic mini-implants coated with zinc oxide (ZnO) nanoparticles. Methods:Forty orthodontic mini-implants were separated into two groups, control group (uncoated mini-implants), and ZnO group (zinc oxide-coated mini-implants). The magnetron sputtering technique was used to cover orthodontic implants with nano-ZnO. In both groups, electron microscope and EDAX (Energy-dispersive X-ray analysis) analysis were used to examine the morphology of ZnO nanoparticles and the chemical composition of them after coating procedure and to assess and visualize the coated mini-implants surface morphology. The coated mini-implants were assessed for cytotoxicity in human lung fibroblast (HLF) using the viable cells yield which was determined by a colorimetric method to evaluate biocompatibility of zincoxide nanoparticles as implantable material. Optical density and percentage of viable cells were compared using one-way analysis of variance with a post-hoc test. Results:In the ZnO group, a homogenous layer of nanoparticles on the mini-implant was demonstrated by Scanning electron microscope (SEM). At lower concentrations of ZnO nanoparticles (12.5 mg/ml to 0.475 mg/ml), the cell viability in the ZnNPs group was generally comparable to the second group. This implies that at lower concentrations, ZnNPs did not significantly affect cell viability. Conclusions: Zinc oxide nanoparticles coated mini-implants generally exhibited insignificant cytotoxicity to human fibroblasts. They can be safely used as a coating of orthodontic mini-implants.